2020
DOI: 10.3390/polym12051100
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pyridylamido Hafnium Complexes for Coordinative Chain Transfer Polymerization

Abstract: The pyridylamido hafnium complex (I) discovered at Dow is a flagship catalyst among postmetallocenes, which are used in the polyolefin industry for PO-chain growth from a chain transfer agent, dialkylzinc. In the present work, with the aim to block a possible deactivation process in prototype compound I, the corresponding derivatives were prepared. A series of pyridylamido Hf complexes were prepared by replacing the 2,6-diisopropylphenylamido part in I with various 2,6-R2C6H3N-moieties (R = cycloheptyl, cycloh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…77 Similarly, the Hf pyridyl amide catalyst 4, well-known for chain shuttling copolymerization, 5 was reported for ethene/propene CCG with dihexylzinc. 15 In a similar way, the Ni α-diimine complex 11c was already reported for ethene CSP. 73 Even if the transfer efficiency with Ni α-diimine complexes is low, the study showed that among this family, the less sterically hindered complexes lead to higher chain transfer efficiencies with Et 2 Zn.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…77 Similarly, the Hf pyridyl amide catalyst 4, well-known for chain shuttling copolymerization, 5 was reported for ethene/propene CCG with dihexylzinc. 15 In a similar way, the Ni α-diimine complex 11c was already reported for ethene CSP. 73 Even if the transfer efficiency with Ni α-diimine complexes is low, the study showed that among this family, the less sterically hindered complexes lead to higher chain transfer efficiencies with Et 2 Zn.…”
Section: Discussionsupporting
confidence: 57%
“…14 The classical Dow's hafnium pyridylamido CCTP catalyst bearing i-Pr substituents (3, Figure 2) was structurally modified (4, substituents R and R 1 , Figure 2) and tested for ethene CCTP and its CCTcoP with propene in order to avoid the deactivation of the original catalyst that may occur during the CCTP process. 15 The R 1 isopropyl moiety affected not only the geometry (distorted vs planar for i-Pr) of complexes but also its catalytic behavior. When using H as a R 1 substituent, the polymerization activity was reduced together with a lower preference for propene addition.…”
Section: Coordinative Chain Transfer Polymerizationmentioning
confidence: 99%
See 3 more Smart Citations